Mapping digital foodscapes: Digital food influencers and the grammars of good food. Issue 117 (December 2020) - Goodman, Michael K.; Jaworska, Sylvia
Highlights: Digital foodscapes are increasingly populated by digital food influencers (DFIs). Different digital platforms offer different affordances to talk about food. DFIs create a series of good food grammars related to clean eating and lifestyle. DFIs position good food within notions of how to be in life. DFIs re-inscribe white, hetero-normative middle- and upper- class privilege. Abstract: Drawing on recent debates around food, space and digital media, this paper introduces and develops the concepts of the digital foodscape and 'good' food grammars . Through a quantitative and qualitative analysis of digital platforms, discourses and personas, we investigate the ways a key set of digital food influencers (DFIs) construct, curate and share the meanings of good food. We first explore who these influencers are, describe what platforms they inhabit, how the variable social media affordances work through these platforms and the notions of good food they construct. We then focus specifically on DFIs' communicative practices on Twitter to analyse the core discourses DFIs produce and those that are taken up by audiences through re-tweets and likes as well as the re-tweeted tweets of DFIs. Overall, our findings suggest that first, good food grammars are being constructed by rule setters beyond the already well-established food personalities and celebrity chefs of the UK's foodscape. Yet, these grammars also re-inscribe a form of white, hetero-normative middle- and upper- class privilege that produces particular grammars of good food. Second, different social media and digital platforms provide space for diverse good food grammars given their variable affordances. Twitter, in particular, is the place where the grammars of DFIs take on non-food themes such as self-empowerment, inspiration, charity campaigning and awareness raising. Third, the notions of good food in DFI grammars revolve around a range of constructions, with the most elevated related to 'clean' eating and/or 'clean' lifestyles that combined healthy, 'free from' diets with fitness regimes and expand DFI grammars – and ultimately their brands – into a more holistic lifestyle brand. This paper's initial empirical and conceptual foray into digital foodscapes and DFIs opens up space for further research on food and digital media within Geography and beyond.